The triatominae species of French Guiana (Heteroptera: Reduviidae) - Jean-Michel Bérenger; Dominique Pluot-Sigwalt; Frédéric Pagès; Denis Blanchet; Christine Aznar (Memorias do Instituto Oswaldo Cruz, 2009)
An annotated list of the triatomine species present in French Guiana is given. It is based on field collections carried out between 1993-2008, museum collections and a literature review. Fourteen species, representing four tribes and six genera, are now known in this country and are illustrated (habitus). Three species are recorded from French Guiana for the first time: Cavernicola pilosa, Microtriatoma trinidadensis and Rhodnius paraensis. The two most common and widely distributed species are Panstrongylus geniculatus and Rhodnius pictipes. The presence of two species (Panstrongylus megistus and Triatoma maculata) could be fortuitous and requires confirmation. Also, the presence of Rhodnius prolixus is doubtful; while it was previously recorded in French Guiana, it was probably mistaken for R. robustus. A key for French Guiana's triatomine species is provided.